Dominantly inherited cerebral dysplasia: arachnoid cyst associated with mild mental handicap in a mother and her son. Issue 12 (December 1997) - Tolmie, J L; Day, R; Fredericks, B; Galea, P; Moffett, A W
Abstract : We report a mother and son who each presented in infancy with hypotonia and global developmental delay. Subsequently, in both subjects, mild mental handicap was diagnosed in association with temporal lobe arachnoid cysts. Mendelian inheritance of this phenotype seems likely and macroscopic cerebral dysplasia in general may be underdiagnosed in people with familial, mild mental handicap.